Zika Virus NS2A-Mediated Virion Assembly - Xianwen Zhang (American Society for Microbiology, 2019)
ABSTRACT The flavivirus virion consists of an envelope outer layer, formed by envelope (E) and membrane (M) proteins on a lipid bilayer, and an internal core, formed by capsid (C) protein and genomic RNA. The molecular mechanism of flavivirus assembly is not well understood. Here, we show that Zika virus (ZIKV) NS2A protein recruits genomic RNA, the structural protein prM/E complex, and the NS2B/NS3 protease complex to the virion assembly site and orchestrates virus morphogenesis. Coimmunoprecipitation analysis showed that ZIKV NS2A binds to prM, E, NS2B, and NS3 (but not C, NS4B, or NS5) in a viral RNA-independent manner, whereas prM/E complex does not interact with NS2B/NS3 complex. Remarkably, a single-amino-acid mutation (E103A) of NS2A impairs its binding to prM/E and NS2B/NS3 and abolishes virus production, demonstrating the indispensable role of NS2A/prM/E and NS2A/NS2B/NS3 interactions in virion assembly. In addition, RNA-protein pulldown analysis identified a stem-loop RNA from the 3ʹ untranslated region (UTR) of the viral genome as an “RNA recruitment signal” for ZIKV assembly. The 3ʹ UTR RNA binds to a cytoplasmic loop of NS2A protein. Mutations of two positively charged residues (R96A and R102A) from the cytoplasmic loop reduce NS2A binding to viral RNA, leading to a complete loss of virion assembly. Collectively, our results support a virion assembly model in which NS2A recruits viral NS2B/NS3 protease and structural C-prM-E polyprotein to the virion assembly site; once the C-prM-E polyprotein has been processed, NS2A presents viral RNA to the structural proteins for virion assembly. IMPORTANCE ZIKV is a recently emerged mosquito-borne flavivirus that can cause devastating congenital Zika syndrome in pregnant women and Guillain-Barré syndrome in adults. The molecular mechanism of ZIKV virion assembly is largely unknown. Here, we report that ZIKV NS2A plays a central role in recruiting viral RNA, structural protein prM/E, and viral NS2B/NS3 protease to the virion assembly site and orchestrating virion morphogenesis. One mutation that impairs these interactions does not significantly affect viral RNA replication but selectively abolishes virion assembly, demonstrating the specific role of these interactions in virus morphogenesis. We also show that the 3ʹ UTR of ZIKV RNA may serve as a “recruitment signal” through binding to NS2A to enter the virion assembly site. Following a coordinated cleavage of C-prM-E at the virion assembly site, NS2A may present the viral RNA to C protein for nucleocapsid formation followed by envelopment with prM/E proteins. The results have provided new insights into flavivirus virion assembly.